Annotation strategy, types, and location in the researcher’s annotated article - Zaihosnita Hood; Noorazean Mohd. Ali (Penerbit Universiti Kebangsaan Malaysia, 2023)
Previous studies have shown that researchers read actively and have their own strategies when reading and writing scientific articles. Annotations are often made during reading, and they help researchers identify important passages and useful information in articles. However, annotations lose value after they are done because researchers forget their intention after making them. The purpose of this article is to identify the strategy, type, and location of annotations in the researcher’s annotated articles. The methodology of this study is a literature review, interview, and analysis of annotated articles by five researchers. The definition of annotation strategies and types is obtained from literature studies. Interviews describe annotation practices or strategies among researchers while reading scientific articles. Analyzed articles that have been annotated by researchers, will show all the researchers' personal annotation types and locations in the articles. The results of this study can be used as a guide for researchers to read scientific articles either printed articles or digital articles to easily track important passages and useful information in the articles.